Effect of Single Corroded Defect Geometry on the Burst Capacity of Grooved Corroded Pipeline Subjected to Internal Pressure - Mohd Khairuddin, Muhammad Amirul Izzwan (IRC, 2018)
Pipeline corrosion causes substancial losses to the economy as well as human life. This project assessed the API 5L X52 steel grade pipeline using Finite Element Analysis and the results were compared with the industrial conventional code DNV-RP-F101. The conventional had been proved as a comprehensive method in determining failure pressure for pipeline subjected to internal pressure and longitudinal comprehensive stress in the presence of single defect, interacting defect and complex shape defect. However, the interaction between single defect and circumferetial groove defect is uncertain. Two types of defects were analysed in this study, namely circumerential groove defect and single defect (assessed as rectangular shape). There are two approaches according to DNV-RP-F101 to be used in determining the failure pressure of pipeline which are calibrated safety factor approach (Part A) and also allowable stress method (Part B). ANSYS Mechanical APDL software was used to perform FEA and validation with previous research shows 10.54 % difference. Since DNV code does not consider the circumferential length of the defect, the results of failure pressure due to the interaction of the two defects show high diference with depth 0.8. The failure pressure obtained from FEA is lower than DNV code. Therefore then can be concluded, DNV code are not comprehensive for determining the failure pressure of interacting defects comprising of circumferential groove and single defect.